Hotel Management Information System / Mok Hei Fung - Mok , Hei Fung (2003)
The proposed system to be developed is a web application Hotel Management Information System. The target target users include guests and staff of the hotel. Thereby, this system does not only serve as a reservation system but also incorporates administration module as well. With online reservation system, guest will be in control of the reservation process from the beginning until the end. Besides, they can make reservation anytime they want with conditions they have Internet access. While for the administrators, they can log on to the system and achieve hotel's database and perform analysis on the data stored. This function can help them to decide hotel's future marketing strategy and attract customer attention by knowing their preferences. For this project, I would follow the waterfall methodology because waterfall model is used if the problem is very well understood: linear sequence of steps that progress from start to finish without revisiting any previous step therefore that methodology is suitable for system where iteration is not necessary. In terms of system development, I proposed to use .NET technology form Microsoft which is ASP.NET and using Microsoft Visual Studio.NET as the web application development tool. Besides that I proposed to use SQL Server 2000 for database management.